Mutational analysis of the p50 subunit of NF-kappa B and inhibition of NF-kappa B activity by trans-dominant p50 mutants. - Bressler, P (1993)
The NF-kappa B family of DNA-binding proteins regulates the expression of many cellular and viral genes. Each of these proteins has an N-terminal region that is homologous to the c-Rel proto-oncogene product, and this Rel homology region defines both DNA binding and protein dimerization properties of the individual proteins. Most of the NF-kappa B family members have been shown to associate with themselves or with each other to form homodimers or heterodimers, and previous studies have shown that dimerization of NF-kappa B factors is necessary to provide a functional DNA binding domain. We have used site-directed mutagenesis to identify regions in the Rel homology domain of the p50/NF-kappa B protein that are important for DNA binding and protein dimerization. Our studies have identified mutations of p50 that interfere with DNA binding only and those that interfere with protein dimerization. Mutations of p50 which disrupt only DNA binding were still able to associate with other members of the NF-kappa B protein family. We demonstrate that such heterodimeric complexes inhibit transcriptional activation mediated in trans through a cis-acting kappa B motif; therefore, we have identified trans-dominant negative mutants of p50.